LEGAL REVIEW OF GIVING MONEY TO SILVER HUMANS ACCORDING TO MUI FATWA AND POSITIVE LAW - ramadi, bagus (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2023)
Silver humans or what are often called “Silver Man Buskers” are the latest phenomenon that we often see at various traffic lights in big cities in recent years. The city of Medan is no exception, currently silver people can still be seen at several corners at red lights. In simple terms, a silver man is a person who entertains road users when a red light is in progress by demonstrating certain movements, such as mining imitating robot movements with the appearance of a body painted silver to attract the attention of those who see it. Not a few of theme were bare-chested and only wore shorts, even with their thin bodies. Apart from being located at red light corner points (traffic lights), there are also those located at tourist attractions. This profession is mostly carried out by those located at tourist attractions. This profession is mostly carried out by those who are already middle-aged, starting form 40 years and above. However, it is not uncommon to see children doin this profession with the aim of making road users concerned and willing to give them money. It turns out that silver man’s action has been around for a long time. It started with the emergence of the phenomenon of babies painted silver in 2012 in the Bandung area, West Java. Tis was then continued with the formation of a community called “Silver Caring Community” which was camouflaged as a donation movement for orphans. However, as time went by, they made this a profession and busked for themselves. The Bandung City Social Service has banned the activities of silver human who claim to be asking for donations for orphans, because they violate Law No. 9 of 1061 concerning the Collection of Money or Goods.